The Use of the Learning Start with Question Model in Writing Information Conclusions on Indonesian Language Education Study Program FKIP UMSU - Oktavia Lestari P (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
In the learning process there are many misunderstandings in concluding the information provided. The use of the learning start with question learning model in writing informational conclusions by students is expected to bring changes for the better. So that an effective learning process occurs when using the learning start with question information model both in the field and at the school where the teacher will teach later. The population of this study were students of semester V. From this total population, a sample of 34 students was determined using a randomized class technique, namely the fifth semester of the morning. This research method is an experimental method using a true experimental design that is to determine the experimental and control groups. The instrument for measuring student learning outcomes is a test of the ability to conclude news content in the form of an essay which is tested after the learning is carried out using the learning start with question model in the experimental class and the lecture method in the control class. Looking for hypotheses using t test with dk = N1 + N2 - 2. Ability to conclude news content after treatment using the learning start with question learning model obtained a mean of 70.29 included in category C (enough). The ability to conclude the content of news after treatment using the lecture method obtained a mean of 59.12 included in category D (less). There is an effect of the learning start with question learning model on the ability to conclude the news content. This effect was tested through hypothesis testing with a confidence level of = 0.05, thitug > ttable or 3.415 > 1.668, which means that in this study the hypothesis was accepted, so it can be concluded that there is a significant effect on the use of the Learning Start With Question Model in Writing Information Conclusions. Students of the Indonesian Language Education Study Program, FKIP UMSU.